Os negros de São Benedito na Igreja do Convento de São Francisco (São Paulo, 1854-1901): resistência e protagonismo em um território de disputas - Luz, Alvaci Mendes da (2022)
This dissertation analyzes the period of the biggest administrative autonomy of the Brotherhood of Glorious St. Benedict in the city of São Paulo (XIX century), during which the church of St. Francis Monastery was under its care. An attempt was made to include the Brotherhood of the Benedict brothers from Largo São Francisco in the historiographical debate about the places of Black Sociability in the capital of São Paulo, the brotherhoods of “colored” men and women and the abolitionist spaces. In the first part, it is evident how much the brotherhoods were present in colonial villages, with singular importance for the protagonism of former slaves and, even, of people still enslaved. Then, it is discussed how the Franciscans used these spaces to propagate their devotion to St. Benedict, as a catechizing strategy. Finally, the path of Brotherhood of St. Benedict is revisited, discussing its performance in the religious, social and political spheres, in a place and time marked by transformations. In methodological terms, it was made documental research, analyzing primary sources – preserved by three archives, those of “Província Franciscana da Imaculada Conceição do Brasil”, of “Cúria Metropolitana de São Paulo” and of “Ordem Terceira de São Francisco da Penitência” – and of periodicals which circulated between the XIX century and the first years of XX century. It was checked that, with the decline of the religious orders in Brazil and the departure of the Franciscans from São Paulo, the Brotherhood of Largo was faced with the possibility of managing the ancient church, encountering a series of disputes to seize its keys and to turn it into a space for the fight against the slaved regime and for Black legitimation, to the point that it turned to be called “St. Benedict Church” and the image of this Saint was placed in the main niche of the main altar